(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, it is said that the object of application of the field of onomology is the category of names in the Uzbek language, and that it can be evaluated as a branch of lexicology, that onomology is evaluated as a unique independent field of linguistics, and that it has linguistic material consisting of its own independent language units.